(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Herein, a novel and successful incorporation of split ring resonators (SRR) as metamaterial on microstrip patch antenna is presented. The antenna is designed by placing 3 x 3 shifted rectangular splitring resonator (SRR) array on a conventional rectangular patch antenna. Furthermore, a comparative study of this novel prototype with the conventional SRR introduced patch antenna shows the influence of the change in position of the square SRR elements on the different parameters especially on the gain of the patch antenna. The gain achieved in case of linearly displaced SRR elements on the patch antenna is increased by almost 70% of the gain of the patch antenna with normal 3 x 3 SRR array incorporation. The rectangular patch antenna design has been made feasible due to the quasistatic resonance property of the split-ring resonators. The measured results are reported at their resonant frequency 2.45 GHz which validates the observation of gain enhancement in this article